Efficacy and Safety of Non-Steroidal Mineralocorticoid Receptor Antagonists in Patients With Chronic Kidney Disease and Type 2 Diabetes: A Systematic Review Incorporating an Indirect Comparisons Meta-Analysis - Jiang, Xinrui; Zhang, Zhengji; Li, Chunlu; Zhang, Shijin; Su, Qiang; Yang, Siyun; Liu, Xin; Hu, Ying; Pu, Xiaofeng (Frontiers in Pharmacology, 2022)
Background: The non-steroidal mineralocorticoid receptor antagonists (MRAs) are promising treatments in patients with chronic kidney disease (CKD) and type 2 diabetes (T2D). We conducted a meta-analysis to explore the efficacy and safety of the non-steroidal MRAs (finerenone, apararenone, esaxerenone) and detect the differences among them. Methods: We searched several databases for eligible randomized controlled trials (RCTs) investigating non-steroidal MRAs versus placebo in patients with CKD and T2D. We performed a conventional meta-analysis separately, and then indirect comparisons for efficacy and safety outcomes were conducted among these included drugs. Results: Eight RCTs with 14450 subjects were enrolled. In patients with CKD and T2D, a greater reduction in urinary albumin-to-creatinine ratio (UACR) (WMD -0.40, 95% CI -0.48 to -0.32, P<0.001), estimated glomerular filtration rate (eGFR) (WMD -2.69, 95% CI -4.47 to -0.91, P= 0.003), systolic blood pressure (SBP) (WMD -4.84, 95% CI -5.96 to -3.72, P < 0.001) and a higher risk of hyperkalemia (RR 2.07, 95% CI 1.86 to 2.30, P < 0.001) were observed in the non-steroidal MRAs versus placebo; there is no significant difference in the incidence of serious adverse events between two groups (RR 1.32, 95% CI 0.98 to 1.79, P = 0.067). Compared with finerenone, esaxerenone showed no significant difference in UACR reduction (WMD 0.24, 95% CI -0.016 to 0.496, P = 0.869); apararenone and esaxerenone showed greater decreases in SBP (WMD 1.37, 95% CI 0.456 to 2.284, P = 0.010; WMD 3.11, 95% CI 0.544 to 5,676, P = 0.021). Conclusions: Despite the moderate increased risk of hyperkalemia, use of non-steroidal MRAs could reduce proteinuria and SBP in patients with CKD and T2D. In terms of renoprotection, esaxerenone and finerenone may have similar effects. Esaxerenone and apararenone may have better antihypertensive effects than finerenone.